‘Colonised by a rich pākehā’: the metaphorical characterisation of the Internet Mana alliance - Peters, Rachel; Hocking, Darryl (Media International Australia, 2022)
In 2014, the Internet Mana alliance unsuccessfully ran in the New Zealand general election gaining just 1.42% of the party vote and failing to secure an electorate seat. The leaders of the alliance attributed their poor election result to the narratives constructed by the mainstream media, which they believed negatively influenced the public?s perception of Internet Mana. This study agrees that the mainstream media was complicit in the alliance?s poor election result, and drawing upon the discourse dynamics framework for metaphor analysis, it shows how these potentially damaging public narratives were predominantly constituted through complex sets of systematic metaphors which together created broader schematic frames or conceptual scenarios and carried certain evaluative and attitudinal perceptions. This analysis shows how systematic metaphors such as the internet mana alliance is a marriage of convenience and the internet mana alliance is a colonial trade were used to construct a negative public narrative.
Keywords: colonisation; elections; mainstream media; political parties